An Analysis of Purchasing and Supply Management Strategies on the Financial Performance of a Firm [A Case Study of Parracombe Packaging] - Vengai, Anna-Maria (Midlands State University, 2017)
The research was used for the analysis and the impact of purchasing and supply strategies implemented by Parracombe packaging and its effect on the financial performance of the firm. The tremendous decline in revenue, cash flow movements, the reduced financial performance and the financial position of the firm made a way for a research to be undertaken. The researcher was conducted with reference to literature that was already done. Closed ended questionnaires and interviews were used in the collection of data. A mixed research approach was used in the undergoing of the study. The research focuses only on the effect of PSM strategies on the performance and excludes other factors such as strategic alignment of functional strategies. The firm which was used for the study is a single manufacturing firm located in Zimbabwe which limited the study in the selection of local and international companies. The selection of the firm only considered the manufacturing excluding the other industries such as the banking sector or the retail industry. The researcher proposes that Parracombe Packaging should concentrate more on how PSM strategies used by the firm affect the firm’s financial performance as it is a major influence on the manufacturing company.